High-contrast 10 PW laser system at the Extreme Light Infrastructure - Nuclear Physics facility - Olivier Chalus; Christophe Derycke; Mathilde Charbonneau; Stanislas Pasternak; Sandrine Ricaud; Peter Fischer; Valeriu Scutelnic; Erhard Gaul; Georg Korn; Saidbek Norbaev; Stefan Popa; Lidia Vasescu; et al. (High Power Laser Science and Engineering)
We are showing a significant enhancement in the temporal contrast by reducing the coherent noise of the 10 PW laser system at the Extreme Light Infrastructure - Nuclear Physics facility. The temporal contrast was improved by four orders of magnitude at 10 picoseconds and by more than one order of magnitude at 50 picoseconds before the main peak. This improvement of the picosecond contrast is critical for the experiments using thin solid targets.